2003
DOI: 10.1111/j.1151-2916.2003.tb03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties of RE1−xRExTiNbO6 [RE = Pr, Nd, Sm; RE′= Gd, Dy, Y] Ceramics

Abstract: The microwave dielectric properties of rare‐earth titanium niobates can be tailored by preparing solid‐solution phases between RETiNbO6 [RE = Pr, Nd, Sm] and RE′TiNbO6 [RE′= Gd, Dy, Y] microwave dielectric ceramics. Dielectric ceramics based on solid‐solution phases RE1−xRE′xTiNbO6 are prepared by the conventional solid‐state ceramic route for different values of x. The ceramic samples are characterized by XRD, SEM, and microwave methods. Ceramics based on RETiNbO6 belonging to aeschynite group show a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Dielectric constant varies from 20.20 to 37.50 and f varies from −45.07 to +42.81 ppm/ • C. For 50-50 composition sintered at 1380 • C, the f is minimum, i.e., −1.9 ppm/ • C and ε r is 33.78. There is a possibility of nonlinear variation in dielec- tric constant and f when the sample is in the region of change of symmetry from aeschynite to euxenite [12]. Hence the composite ceramic 50PTT of this series is the most suitable material as a dielectric resonator.…”
Section: Resultsmentioning
confidence: 98%
“…Dielectric constant varies from 20.20 to 37.50 and f varies from −45.07 to +42.81 ppm/ • C. For 50-50 composition sintered at 1380 • C, the f is minimum, i.e., −1.9 ppm/ • C and ε r is 33.78. There is a possibility of nonlinear variation in dielec- tric constant and f when the sample is in the region of change of symmetry from aeschynite to euxenite [12]. Hence the composite ceramic 50PTT of this series is the most suitable material as a dielectric resonator.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, highest dielectric quality factors have been found in AðB 0 1=3 B 00 2=3 ÞO 3 ceramic systems, mainly BaðMg 1=3 Nb 2=3 ÞO 3 and BaðMg 1=3 Ta 2=3 ÞO 3 [5,6]. More recently, oxides containing rare earth ions such as AðRE 1=2 M 1=2 ÞO 3 [7][8][9][10][11][12] and REðTiMÞO 6 [13][14][15][16][17][18], where A is commonly an alkaline earth metal, RE is an yttrium or rare-earth ion and M is a transition metal (usually Ta þ5 or Nb þ5 ), have been extensively studied showing good properties for microwave applications.…”
Section: Introductionmentioning
confidence: 96%
“…The principal difference between Ln 3+ in these structures is that in aeschynite orthorhombic structure they lie in closely connected chains where as in euxenite orthorhombic structures they lie on densely packed parallel planes [21]. Solomon et al [22] and Surendran et al [23,24] reported that by making a suitable solid solutions of both aeschynite and euxenite structures, it is possible to get compositions having low τ f and desirable microwave dielectric properties. Recently Oishi et al [25] reported the effects of Ta substitution for Nb and Zr substitution for Ti on the microwave dielectric properties and crystal structure of Sm(Nb 1−x Ta x )(Ti 1−y Zr y )O 6 ceramics.…”
Section: Introductionmentioning
confidence: 96%